2021
DOI: 10.3390/rs13132545
|View full text |Cite
|
Sign up to set email alerts
|

Can Vegetation Indices Serve as Proxies for Potential Sun-Induced Fluorescence (SIF)? A Fuzzy Simulation Approach on Airborne Imaging Spectroscopy Data

Abstract: In this study, we are testing a proxy for red and far-red Sun-induced fluorescence (SIF) using an integrated fuzzy logic modelling approach, termed as SIFfuzzy and SIFfuzzy-APAR. The SIF emitted from the core of the photosynthesis and observed at the top-of-canopy is regulated by three major controlling factors: (1) light interception and absorption by canopy plant cover; (2) escape fraction of SIF photons (fesc); (3) light use efficiency and non-photochemical quenching (NPQ) processes. In our study, we propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 86 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…Whereas the differences in VIs and LAI between CL and CR during the summer were observed to be significant, indicating the importance of hydrological regimes and fluctuations of water table depth for peatland vegetation (Supplementary Table S2) [18]. The observation of various VIs is considered an efficient method for detecting the changes in the plant physiology at the ecosystem level, but VIs have their limitations; therefore, other indices such as SIF have been developed that can better present the physiological status of the vegetations [15,36]. In this study, NDVI, EVI, and NIRv showed a seasonal pattern for both the studied sites and was observed to be highly correlated with modeled LAI, but the correlation with measured LAI was observed to be poor (Figure 5), which can be again explained through the non-consideration of mosses and part of the litter interference in measured LAI.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the differences in VIs and LAI between CL and CR during the summer were observed to be significant, indicating the importance of hydrological regimes and fluctuations of water table depth for peatland vegetation (Supplementary Table S2) [18]. The observation of various VIs is considered an efficient method for detecting the changes in the plant physiology at the ecosystem level, but VIs have their limitations; therefore, other indices such as SIF have been developed that can better present the physiological status of the vegetations [15,36]. In this study, NDVI, EVI, and NIRv showed a seasonal pattern for both the studied sites and was observed to be highly correlated with modeled LAI, but the correlation with measured LAI was observed to be poor (Figure 5), which can be again explained through the non-consideration of mosses and part of the litter interference in measured LAI.…”
Section: Discussionmentioning
confidence: 99%
“…Although aerial thermal data has been previously applied in peatland research (Kopeć et al, 2016), further research into the potential use of airborne thermal data in assessing peatland vegetation conditions is recommended. To date, there have been few works in Poland using spectral data in peatland monitoring (Bandopadhyay et al, 2021(Bandopadhyay et al, , 2019. However, none has attempted to collate palaeoecological, dendrochronological, and remote sensing data.…”
Section: Current Condition Of the Peatland Vs Remote Sensing And Dend...mentioning
confidence: 99%
“…Membership values computed from VI 20 or BT 20 variables were combined using the fuzzy overlay operator GAMMA since it has been reported to offer a balance between over and underestimation of fluorescence radiance [80,81]. µ_γ (x) = 〖[µ_SUM (x)]〗^γ * 〖[µ_PRODUCT (x)]〗^(1 − γ) Then a linear model was fit using the integrated membership values as a predictor of SIF λ : (F_λ) = b_0 + b_1 µ_γ (x) Fuzzy modelling was applied to 5 and 20 m spatial resolution data, and then these maps were gridded to 300 m pixels.…”
Section: Normalized Entropymentioning
confidence: 99%